Norm Fragmentation in Indonesia's Offshore Carbon Capture and Storage Regulation: A National and International Legal Analysis - M Misbahul Mujib (UIN Sunan Kalijaga Yogyakarta, 2025)
The development of offshore Carbon Capture and Storage (CCS) has become an important component of Indonesia’s climate mitigation and energy transition strategy, particularly following the enactment of Presidential Regulation No. 14 of 2024 and Minister of Energy and Mineral Resources Regulation No. 2 of 2023. Despite these regulatory developments, offshore CCS governance remains dispersed across environmental, maritime, energy, climate, and international legal regimes, creating challenges for legal coherence and effective marine environmental governance. This study examines the forms of norm fragmentation within Indonesia’s offshore CCS regulatory framework and evaluates their implications for legal certainty and sustainable offshore carbon storage governance. It employs normative legal research using statute and conceptual approaches. The analysis is grounded in Regulatory Fragmentation Theory and supported by institutional mapping and a comparative regulatory matrix to identify overlaps, inconsistencies, and gaps among relevant legal instruments. Primary legal materials consist of Indonesian legislation and international legal instruments, particularly UNCLOS 1982 and the London Protocol framework. The findings reveal five principal forms of norm fragmentation: environmental governance fragmentation, maritime and spatial governance fragmentation, licensing and institutional fragmentation, liability and long-term monitoring fragmentation, and fragmentation between domestic offshore CCS norms and international marine environmental obligations. These forms of fragmentation arise from overlapping authorities, insufficient integration of offshore CCS within marine spatial planning, inconsistent monitoring and liability arrangements, and incomplete alignment with international legal frameworks governing offshore carbon storage and transboundary CO₂ transport.This study contributes to the emerging scholarship on offshore CCS governance by developing a norm-fragmentation framework that integrates environmental, maritime, energy, and international law perspectives. It concludes that legal harmonization, stronger institutional coordination, and greater alignment with international standards are essential to support sustainable offshore CCS development in Indonesia.